Dyschromatopsia: a comprehensive analysis of mechanisms and cutting-edge treatments for color vision deficiency - Yang, Zihao; Yan, Lin; Zhang, Wenliang; Qi, Jia; An, Wenjing; Yao, Kai (Frontiers in Neuroscience, 2024)
Color blindness is a retinal disease that mainly manifests as a color vision disorder, characterized by achromatopsia, red-green color blindness, and blue-yellow color blindness. With the development of technology and progress in theory, extensive research has been conducted on the genetic basis of color blindness, and various approaches have been explored for its treatment. This article aims to provide a comprehensive review of recent advances in understanding the pathological mechanism, clinical symptoms, and treatment options for color blindness. Additionally, we discuss the various treatment approaches that have been developed to address color blindness, including gene therapy, pharmacological interventions, and visual aids. Furthermore, we highlight the promising results from clinical trials of these treatments, as well as the ongoing challenges that must be addressed to achieve effective and long-lasting therapeutic outcomes. Overall, this review provides valuable insights into the current state of research on color blindness, with the intention of informing further investigation and development of effective treatments for this disease.